Lei da liberdade econômica e as (indevidas) modificações nos contratos do código civil - Merighi, Ronaldo Guaranha (2024)
The objective of this thesis is to analyze the modifications promoted by Law No. 13,874/2019, Law of Economic Freedom, in the Civil Code, in the part related to contracts. This analysis starts from the premise that the law in question presented itself as an instrument of Economic Law, which is why the research began with the analysis of this branch of Law and the intersections between it and Contract Law. We emphasize the importance of this conformation, before the idea of a Constitutional Civil Law, that is, that cannot ignore the Major Law at the apex of our legal system. Moreover, when considering the Constitution of 1988 as an Economic Constitution, any amendment of an infra-constitutional law that intends to translate the commands of its Article 170, owes it total obedience. In the analysis of Contract Law, we go through the whole evolution of the concept of contract and its placement as an instrument of generation and distribution of wealth in a Social State, such as the Brazilian one. Always in order to check the timeliness and usefulness of the vision implemented by the Legislature of the Economic Freedom Act. We evaluate with the same search the principle basis of the Code itself and of its contractual chapter. We seek to connect the constitutional values of the dignity of the human person, sociality, free enterprise and reduction of inequalities with the social function of the contract, frontally affected by Law No. 13.874/2019. Based on our research, we conclude that the mentioned law distanced itself from constitutional ideology by seeking to elevate free enterprise to a prominent position instead of reconciling it with other principles of the Supreme Law. Thus, it attempted to instill a voluntarist perspective into contracts, equally incompatible with the principled foundation of the Civil Code of 2002. It sought to diminish the interpretative powers of the judge by resurrecting interpretative rules from the Commercial Code of 1850 and to constrain the social function of the contract by excluding "due to" from Article 421. It aimed to establish a nonexistent and unnecessary principle of minimal intervention in contracts and, also unnecessarily, reinforce the exceptionality of contractual revision, based on the unproven premise of excessive judicial intervention in contracts. The Economic Freedom Law only succeeded in modifying the term "freedom to contract" to "contractual freedom" (Article 421's heading) and, although with a different intention, did not err in stating that civil and business contracts can be asymmetrical, even when considered equal (the heading of Article 421-A). As reflections we submit for discussion on the topic.